DESIGN OF A HEALING GARDEN WITH A GREEN ARCHITECTURE APPROACH [AT OG HOSPITAL BINJAI] - Rayhani Deah Putri; Abdi Sugiarto (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The Healing Garden is a garden that specifically provides a sense of protection and comfort aimed at improving health outcomes for patients, families and hospital staff. Hospital. This hospital is located on Jl. Sport No. 1, Timbang Langkat, District. East Binjai., Binjai City, North Sumatra. This public hospital, which is accredited with 5 stars from the Hospital Accreditation Commission (KARS) and is now a type D hospital, provides treatment for general illnesses as well as internal medicine (internship). This approach to green architecture.